Pengembangan Bahan Ajar Menulis Teks Deskripsi Bermuatan Nilai Moral Untuk Peserta Didik Kelas Vii Smp Unggulan An-Nur Hidayatullah Talok - Baiquni, Muhammad Masykur; Hanafi, Roy (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2024)
This research is a development study to create teaching materials to compile descriptive texts that contain moral values for students of SMP grade VII An-Nur Hidayatullah Talok. This teaching material is made based on the principles of creating teaching materials. In addition, the language of the material is adjusted to the student's level of thinking, so that students no longer have difficulty in writing descriptive texts. The purpose of this study is to improve the quality of students' achievement or learning outcomes in the description text material. And an interest in moral values can arise even in a small environment such as the home environment through a lot of conversation and politeness. This type of research uses the research and development method (Research and Development), which is a method that produces a product and then tests the effectiveness of the product. This study uses the Borg & Gall model which is clarified into seven stages including preliminary study, planning, product development, product validation, design revision, product trial and revision. This research develops teaching materials in learning to write valueloaded description texts for junior high school grade VII. The results of the research on the validation of media experts obtained a percentage of 83.75%. Validation of material experts gets a percentage of 90%. The results of the small group trial got a percentage of 88.4% while the results of the large group trial got a percentage of 93.8%.